2008
DOI: 10.1152/ajpcell.00060.2008
|View full text |Cite
|
Sign up to set email alerts
|

mCLCA4 ER processing and secretion requires luminal sorting motifs

Abstract: Ca ϩ -activated Cl Ϫ channel (CLCA) proteins are encoded by a family of highly related and clustered genes in mammals that are markedly upregulated in inflammation and have been shown to affect chloride transport. Here we describe the cellular processing and regulatory sequences underlying murine (m) CLCA4 proteins. The 125-kDa mCLCA4 gene product is cleaved to 90-and 40-kDa fragments, and the NH2-and COOH-terminal fragments are secreted, where they are found in cell media and associated with the plasma membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Moreover, subsequent findings were more consistent with the proposal that CLCA1 effects on chloride transport may be based on increasing conductance of endogenous CaCCs (40). It further appears (based on analysis of crude membrane preparations) that secreted CLCA proteins are first processed intracellularly into N-terminal and C-terminal peptide fragments (18,39,(41)(42)(43)(44). The present findings support this alternative proposal as well, in that CLCA1 is colocalized within the cell along with MUC5AC in secretory granules and is secreted to the apical cell surface in response to IL-13.…”
Section: Figuresupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, subsequent findings were more consistent with the proposal that CLCA1 effects on chloride transport may be based on increasing conductance of endogenous CaCCs (40). It further appears (based on analysis of crude membrane preparations) that secreted CLCA proteins are first processed intracellularly into N-terminal and C-terminal peptide fragments (18,39,(41)(42)(43)(44). The present findings support this alternative proposal as well, in that CLCA1 is colocalized within the cell along with MUC5AC in secretory granules and is secreted to the apical cell surface in response to IL-13.…”
Section: Figuresupporting
confidence: 77%
“…In that regard, even the initial bioinformatic (16) and experimental data (17,18,39) indicated that CLCA proteins generally lack the structural features to form ion channels by themselves, since they either contain only a single transmembrane anchor or exhibit secretion from the cell in soluble form. Moreover, subsequent findings were more consistent with the proposal that CLCA1 effects on chloride transport may be based on increasing conductance of endogenous CaCCs (40).…”
Section: Figurementioning
confidence: 99%
“…1B). Because our data and previous studies indicated that CLCA proteins are processed intracellularly (7,8,21,22), we also analyzed CLCA1 retrieved from cell lysates to investigate the possibility of sequential processing. This sample displayed the same cleavage site as the fully secreted proteins found in supernatants.…”
Section: Clca Proteins Share a Common Cleavage Site-proteolyticmentioning
confidence: 99%
“…A revised scheme for the domain structure for mouse and human CLCA proteins is provided in Figure 3, and an annotated analysis of amino acid sequence for these proteins is provided in Figure 4. This updated analysis implies that the CLCA proteins are soluble secreted molecules (2931) with the exception of a subset of CLCA proteins that contain a C-terminal membrane-anchoring region (32, 33). This anchoring region takes the form of a transmembrane alpha-helix or GPI anchor that lacks the structural requirements to function as an ion channel itself (15, 29).…”
Section: Background Biochemistrymentioning
confidence: 99%
“…In each case, a precursor 120-kDa glycoprotein is cleaved to produce approximately 85-kDa N-terminal and 35-kDa C-terminal products, both of which contain numerous N-linked glycosylation sites (30, 33, 38). For hCLCA1, mClca3, and mClca4 (which have no identifiable transmembrane region), both the N- and C-terminal products are secreted into the media when expressed in human cell lines (2931). In similar experiments with hCLCA2 (which has a transmembrane region), the N-terminal product is released into the media while the C-terminal product remains cell surface associated (32).…”
Section: Background Biochemistrymentioning
confidence: 99%